Research on design and implementation of innovative UGV modular platform in mine action programs - Dženan Ćosić; Alan Ćatović; Muamer Delić; Jasna Mujkić (Defense and Security Studies)
This research paper focuses on the development of an innovative system applying the UGV (Unmanned Ground Vehicle) modular platform in the fields of humanitarian demining, where the scientific research process demonstrates the multifunctional application of such systems, or similar ones, in civil protection sectors. The use of the UGV platform enables more efficient mission completion in scenarios where human lives are directly at risk, such as demining operations. The UGV platform, with its modular design and development approach, represents a modern method for the advancement of such systems, offering multi-operation and multifunctional applications.